Broadway musicals show by show - Green, Stanley (Applause Theatre & Cinema Books, 2014)
This updated edition of one of the bestselling and most comprehensive Broadway reference books, first published in 1985, has been expanded to include many of the most important and memorable productions of American musical theater, including revivals. Chronologically arranged, beginning with The Black Crook in 1866, the eighth edition adds new entries and photos on numerous musicals from recent years, including Priscilla, Queen of the Desert ; The Book of Mormon ; Spider-Man: Turn Off the Dark ; Once ; Newsies: The Musical ; Annie (revival); Rodgers & Hammerstein's Cinderella ; Kinky Boots ; A Night with Janis Joplin ; and A Gentleman's Guide to Love and Murder . Broadway Musicals, Show-by-Show features a wealth of statistics and inside information, plus critical reception, cast lists, pithy commentary about each show, and numerous detailed indexes that no Broadway fan will want to be without